Association of sugar-sweetened beverages with executive function in autistic children - Pan, Shuolin; Wang, Xin; Lin, Lizi; Chen, Jiajie; Zhan, Xiaoling; Jin, Chengkai; Ou, Xiaoxuan; Gu, Tingfeng; Jing, Jin; Cai, Li (Frontiers in Nutrition, 2022)
The association between sugar-sweetened beverages (SSB) consumption and executive function (EF) among typically developing (TD) children has been investigated in previous studies but with inconsistent results. Furthermore, this relationship has been less investigated among autistic children who perform worse in EF compared to TD children. In this study, we aimed to investigate the association between SSB consumption and EF in autistic children, and whether the association between SSB and EF in autistic children is different from that in TD children. We recruited 106 autistic children and 207 TD children aged 6-12 years in Guangzhou, China. Children’s EF was assessed by using the Chinese version of parent-reported Behavior Rating Inventory of Executive Function, Stroop Color-Word Test, and working memory subscales of the Chinese version of Wechsler Intelligence Scale for children, Fourth edition. Meanwhile, we assessed children’s dietary intake and SSB consumption with a validated Food Frequency Questionnaire. In this study, 70 (66.0%) autistic children consumed SSB and 20 (18.9%) of them consumed more than 2 servings SSB a week. Among autistic children, over 2 servings per week SSB consumption was associated with poorer performance in emotional control (β=7.20, 95% confidence interval [CI]: 0.94 to13.46) and plan/Organize (β=6.45,95% CI:0.27 to 12.63). The association between over 2 servings/week SSB consumption and emotional control among autistic children was significantly different from that among TD children (βASD=7.20; βTD=-3.09, Z= 2.72, P=0.006). Results of this study show that SSB consumption was associated with impairment in some subscales of EF in autistic children. Furthermore, the association between SSB and EF in autistic children might be different from that in TD children.